PENGARUH TINGKAT PENDIDIKAN, PENGETAHUAN AKUNTANSI PEMILIK, DAN PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UMKM - Dyah Pitaloka; Nur Diana; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to analyze the influence of educational background, owner's accounting knowledge, and training in preparing financial statements on small and medium micro businesses financial statements. The population in this study was the small and medium micro businesses in the field of footwear in the district of Sooko, Mojokerto Regency. This study uses small businesses and 91 small business shoes selected by the method of Purposive Sampling. The analytical model used in this study is multiple linear regression. The results of this study show that educational variables, owners' accounting knowledge and education in preparing financial statements can simultaneously have a large impact on the financial statements of small and medium-sized enterprises.Keywords: small and medium micro businesses Financial Reports, Educational Background, Accounting Knowledge, and Training on Financial Report Preparation